THE ROLE OF TEACHERS IN INCREASING INTEREST IN LEARNING IN CLASS V CHILDREN AT SDN 38/II PAUH AGUNG: PERAN GURU DALAM MENINGKATKAN MINAT BELAJAR ANAK KELAS V DI SDN 38/II PAUH AGUNG - Maria Ulfa; Apdoludin; Dhini Mufti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The problem in this research is that students' interest in learning is still relatively low. Some students seemed unfocused, paid little attention to the teacher, and were busy playing alone during the lesson, especially during the second lesson. This indicates a lack of a pleasant learning atmosphere and a lack of active participation from students. This low interest in learning can also be caused by the teacher's teaching style which is monotonous, less varied, and does not adapt to the needs and characteristics of students. Students' moods, as well as limited facilities and infrastructure at school, are also factors that influence their enthusiasm for learning. Students' interest in learning can be reflected in the way they follow lessons, pay attention to teachers, and interact in the learning process. In carrying out their duties, teachers have various important roles such as educators, instructors, mentors, leaders, motivators, facilitators and evaluators. According to Slameto in Rifal (2022), teachers must be able to provide encouragement, inspiration and motivation to their students so that they feel enthusiastic about developing their potential. Teachers must continue to develop their professionalism so that they are able to carry out their roles effectively according to the demands of the times and the needs of students